PROSES PEMANTAPAN LITERASI NUMERASI MELALUI KEGIATAN EKSTRAKURIKULER ARITMATIKA DI SD ISLAM TIRTAYASA - Khanza Shofiana; Encep Andriana; Siti Rokmanah (STKIP Subang, 2023)
Numeracy literacy skills are very important for students to have. Because these skills can help someone to gain the basic skills needed to achieve success in life. By having good numeracy literacy skills, students will be better prepared to face current developments, especially in the 21st century which is relatively fast and dynamic. Apart from that, students are able to think rationally, systematically and critically in solving existing problems. This research aims to describe the process of strengthening numeracy literacy through arithmetic extracurricular activities at Tirtayasa Islamic Elementary School. This research uses qualitative/descriptive methods. This research directly involved the supervisor of extracurricular arithmetic activities as a research participant. The data obtained was through interviews and observations. The research results show that Tirtayasa Islamic Elementary School has provided guidance to students to improve their numeracy literacy skills through arithmetic extracurricular activities.